A comparison of the analgesic efficacy of local infiltration analgesia vs. intrathecal morphine after total knee replacement: A randomised controlled trial. Issue 4 (April 2019) - McCarthy, Denise; McNamara, John; Galbraith, John; Loughnane, Frank; Shorten, George; Iohom, Gabriella
Abstract : BACKGROUND: Local infiltration analgesia (LIA) is an effective pain management technique following total knee arthroplasty (TKA). OBJECTIVE: To investigate if LIA provides better analgesia for patients undergoing unilateral TKA than intrathecal morphine. DESIGN: Randomised controlled trial. SETTING: Single tertiary referral centre. PATIENTS: Consecutive American Society of Anesthesiologists Physical Status I to III patients scheduled to undergo unilateral TKA were randomised to two groups. INTERVENTION: The control group received spinal anaesthesia with intrathecal bupivacaine and preservative-free morphine 0.3 mg. The intervention group received opioid-free spinal anaesthesia with bupivacaine, followed by intra-operative infiltration of the knee with levobupivacaine 2 mg kg −1 and adrenaline 0.5 mg diluted to a volume of 100 ml with 0.9% saline. An intra-articular catheter was placed during surgery and used to give a bolus of 15 ml of levobupivacaine 0.5% on the morning of the first postoperative day. MAIN OUTCOME MEASURES: Visual analogue scale (VAS) scores for pain were assessed repeatedly for 48 h postoperatively, at rest and on passive knee flexion to 30°. The primary outcome was VAS scores for pain at rest and on movement at 24 postoperative hours. Secondary outcomes were VAS scores at rest and on movement at 2, 6, 12 and 48 postoperative hours, opioid consumption, degree of active flexion of operative knee achieved in the first 48 h and the incidence of opioid-related side effects. RESULTS: Forty three patients completed the study. Mean (± SD) VAS scores for pain at 24 h were lower in the intervention group than the control group at rest; 16.43 (± 20.3) vs. 37.2 (± 33.6), ( P = 0.029). VAS scores for pain at 24 h on movement were also lower in the intervention group vs. the control group; 39.1 (± 22.8) vs. 57.0 (± 30.9), ( P = 0.037). VAS scores were also lower on movement; 25.9 (± 16.8) vs. 40.5 (± 24.0), ( P = 0.028) at 48 h. CONCLUSION: We conclude that LIA conferred superior analgesia compared with intrathecal morphine 0.3 mg at 24 and 48 h following TKA. TRIAL REGISTRATION: Clinicaltrials.gov identifier: NCT01312415. Abstract : Supplemental Digital Content is available in the text